2017
DOI: 10.1155/2017/2682149
|View full text |Cite
|
Sign up to set email alerts
|

Corynebacterium striatumBacteremia Associated with a Catheter-Related Blood Stream Infection

Abstract: A 49-year-old woman visited our emergency department because of exertional dyspnea due to severe left ventricular functional failure. It progressed to disseminated intravascular coagulation and disturbance of consciousness on day 67 of admission. Gram-positive bacilli were detected from two different blood culture samples on day 67 of admission. An API-Coryne test and sequencing (1~615 bp) of the 16S rRNA gene were performed, and the strain was identified as Corynebacterium striatum. The bacterium was detected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…Corynebacterium striatum has been increasingly associated with severe infections in both immunocompetent and immunocompromised hosts [3, 4]. However, C. striatum isolates have been included among the etiologic agents of bacteremia with or without central venous catheter (CVC) in place [5, 6], endocarditis [7], breast abscesses [8], septic arthritis [2], osteomyelitis [4] and several other invasive diseases. In addition, studies have evidenced C. striatum as an emerging multidrug-resistant (MDR) pathogen related to nosocomial outbreaks in several countries [916].…”
Section: Introductionmentioning
confidence: 99%
“…Corynebacterium striatum has been increasingly associated with severe infections in both immunocompetent and immunocompromised hosts [3, 4]. However, C. striatum isolates have been included among the etiologic agents of bacteremia with or without central venous catheter (CVC) in place [5, 6], endocarditis [7], breast abscesses [8], septic arthritis [2], osteomyelitis [4] and several other invasive diseases. In addition, studies have evidenced C. striatum as an emerging multidrug-resistant (MDR) pathogen related to nosocomial outbreaks in several countries [916].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have increasingly reported that the following strains are important causes of infection: C. striatum, C. jeikeum, C. amycolatum, C. urealyticum, C. afermentans, C. ulcerans, C. minitissimum, C. propinquum, and C. pseudodiphtheriticum 3 . Studies investigating various clinical specimens have indicated that between 44% and 71% of patients with Corynebacterium bacteremia have true infections [13][14][15] .…”
Section: Discussionmentioning
confidence: 99%
“…are normal flora bacteria in human skin and mucous membranes. When isolated from clinical specimens they cause serious infections and nosocomial outbreaks in critically ill immunocompromised patients, for example in those with end-stage cancer, hematologic malignancy, or who have prosthetic devices or stayed for prolonged periods in a hospital or nursing homes [3][4][5] . Nosocomial outbreaks, especially due to Corynebacterium striatum, are increasing in both industrialized and developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…xerosis, C. jeikeium, C. macginleyi, C. urealyticum, C. pseudodiphtheriticum and C. freneyi, have appeared recently as opportunistic pathogens in immunocompromised patients, in patients with hematologic malignances and in the critically ill (3,4). Corynebacterium striatum colonizes prosthetic devices, catheter tips and ventilator tubes (3), and so most cases where C. striatum is isolated as the culprit pathogen are nosocomial infections involving the exit sites of central venous catheters, conjunctivitis, chorioamnionitis, peritonitis and pyogenic granuloma (1), catheter related blood stream infections (4), pleuropneumonia, meningitis, endocarditis, osteomyelitis and arthritis (5).…”
Section: Discussionmentioning
confidence: 99%